AKSIOLOGI MANUSIA DALAM PERKEMBANGAN PENDIDIKAN ISLAM(PERSPEKTIF IBNU KHALDUN) - Annisa Suci Mariana; Hidayatus Sholikha; Muhammad Yusron Maulana El-Yunusi (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2025)
This research aims to analyze humans from the perspective of Ibn Khaldun's thoughts. Who is a great figure and leader of the Islamic religion islamic education in the word Research data was analyzed using literature study the data source is the journal of philosophical thought contains Ibn Khaldun's thoughts about humans and the development of Islamic education. The results of the analysis show that Ibn Khaldun's thoughts are in line with people's thoughts which are part of the axiology and philosophy of the Islamic religion. Of the four educational methods according to Ibn Khaldun, they can be divided into the memorization method, discussion method, exemplary method, and repetitionmethod